Re-affirming the role of technical vocational education and training in the development of the Jamaican economy - Hutton, Disraeli (2008)
Presents an overview of the development of technical vocational education internationally and its formal introduction in the Jamaican school system in the 1960s. Discusses some of the factors which determine the value of technical vocational education and establishes a clear link between the development of world economies and the resurgence of technical vocational education.